Computationally efficient permanent magnet traction motor loss assessment. Issue 6 (5th November 2018) - Sarigiannidis, Athanasios; Beniakar, Minos; Kladas, Antonios
Abstract : Purpose: This paper aims to introduce a computationally efficient hybrid analytical–finite element (FE) methodology for loss evaluation in electric vehicle (EV) permanent magnet (PM) traction motor applications. In this class of problems, eddy current losses in PMs and iron laminations constitute an important part of overall drive losses, representing a key design target. Design/methodology/approach: Both surface mounted permanent magnet (SMPM) and double-layer interior permanent magnet (IPM) motor topologies are considered. The PM eddy losses are calculated by using analytical solutions and Fourier harmonic decomposition. The boundary conditions are based on slot opening magnetic field strength tangential component in the air gap in the SMPM topology case, whereas the numerically evaluated normal flux density variation on the surface of the outer PM is implemented in the IPM case. Combined analytical–loss evaluation technique has been verified by comparing its results to a transient magnetodynamic two-dimensional FE model ones. Findings: The proposed loss evaluation technique calculated the total power losses for various operating conditions with low computational cost, illustrating the relative advantages and drawbacks of each motor topology along a typical EV operating cycle. The accuracy of the method was comparable to transient FE loss evaluation models, particularly around nominal speed. Originality/value: The originality of this paper is based on the development of a fast and accurate PM eddy loss model for both SMPM and IPM motor topologies for traction applications, combining effectively both analytical and FE techniques.